Enhancing Mass Lesion of the Sphenoid: Atypical Presentation of Ongoing Pneumatization - Deepak Vallabhaneni; Anthony Mohamed; Zain Badar; Rajiv Mangla (Case Reports in Pediatrics)
Sinus pneumatization is a complex variable process that begins in early life and continues for many years. We present a case of a 6-year-old boy with progressive headaches and neurologic symptoms suggestive of intracranial pathology. The presence of enhancing tissue within the sphenoid sinus created a diagnostic dilemma which leads to a transsphenoidal biopsy. Knowledge of imaging characteristics associated with incomplete pneumatization can help differentiate it from more ominous skull base pathology and prevent unnecessary testing. We describe four-year imaging follow-up in a patient with incomplete pneumatization of the sphenoid sinus presenting as an enhancing mass lesion with subsequent follow-up imaging demonstrating gradual regression and increased aeration of the sphenoid sinus.